ROLE OF REGULATORY REFORMS FOR DEVELOPMENT AND QUALITY IMPROVEMENT OF THE CONSTRUCTION SECTOR IN MONTENEGRO - Jocovic, Mijat; Milović, Nikola; Melović, Boban (Journal of Applied Engineering Science, 2016)
The authors of this paper researched the influence of the quality of the regulatory rules on the construction sector in Montenegro. The authors noticed and clearly pointed out that the significance of construction for, the total economy of Montenegro, its influence on other economic activities and participance in the social gross product of the country entirely justifies the need for constant attention of the politics creators. Key issues in the legal framework which negatively influenced the improvement of competitiveness of this sector and national economy are noticed and clearly pointed out in this paper. As the most significant, the following ones are identified: trend of provisions instability, existence of mutual collision of laws and sublegal acts, regulation of spatial planning, issuing building permits, property registration and system of public procurement. After having analyzed the changes in the regulatory frame and their affect on improving the position of Montenegro on the lists of competitiveness in international organizations, the authors make a general conclusion that necessity of regulatory reform with providing a predictable and functional system is one of the basic preconditions for further development of this sector.